Synthesis of N-Tetradecyl-1,10-phenathrolinium-Based New Salts for Biological Applications - Atakilt Abebe; Minaleshewa Atlabachew; Misganaw Liyew; Elsabet Ferede (Bioinorganic Chemistry and Applications)
New organic salts were synthesized by quaternizing 1,10-phenanthroline using 1-bromotetradecane. The first step yielded an organic salt of formula [C26H37N2]Br. Anion exchange reaction using Li[(CF3SO2)2N] resulted in a more stable salt of formula [C26H37N2][(CF3SO2)2N]. The organic salts were investigated by spectrometry (1H, 13C, 19F NMR, X-ray photoelectron spectroscopy (XPS), UV-Vis, and matrix-assisted laser desorption/ionization mass spectroscopy (MALDI MS), CHNSBr elemental analysis, and thermal analysis (TGA and DSC). The thermal characterization showed the melting and decomposition points of [C26H37N2][(CF3SO2)2N] to be 48°C and 290°C, respectively, which indicates it is an ionic liquid with large liquidus range. The biological activities of the salts were investigated against two Gram-positive (Staphylococcus aureus and Streptococcus pyogenes) and two Gram-negative (Escherichia coli and Klebsiella pneumoniae) bacteria, and they are found to be active against all of them. They were compared with [Cu(1,10-phenanthroline)2Cl]Cl. They are found more active against the Gram-negative bacteria. The salts demonstrated minimum inhibitory concentration as low as 50 µg/L. These results suggest the synthesized salts can be considered as a better alternative to certain transition metal complex drugs. This minimizes the concern of introducing metal ions into the organism.